Conventional interstrain mating between Pleurotus pulmnarius (FR) quel and Pleurotus citrinopileatus singer an yiled performance of selected hybrids / Rosnina Abdul Gani - Rosnina , Abdul Gani (2017)
Oyster mushrooms (Pleurotus spp.) are cultivated widely at present as it ranked second after the button mushroom. There is a growing demand for new and improved mushroom hybrids with better features including yield. The present study was conducted with the objectives to improve the characteristics and yield of Pleurotus pulmonariius and P. citrinopileatus by interstrain mating between P. pulmonarius and P. citrinopileatus monokaryon cultures. Ten single spore isolates of both parental strains were crossed in all combinations for the purpose of developing new hybrids. From a total of one hundred possible pairings, five hybrids were obtained which produced sporophores with P. pulmonarius dominant characteristics and six hybrids had sporophores features similar to P. citrinopileatus. Three dikaryotic isolates were evaluated for duration of spawn run, yield and biological efficiency. Further analysis of the mating types and compatible mating of the isolates of dikaryons from the positive mating were confirmed and differentiated. Macroscopic features of the new genotype sporophores were compared to parental strains and analyzed using DNA molecular work. The DNA sequences of five hybrids showed high genetic homology with dominant parent P. pulmonarius which generated a bootstrap value of 94 %. Six hybrids were found to be in the same clade as the other parent, P. citrinopileatus with a bootstrap value of 99 %. High bootstrap values indicated high genetic homology between hybrids and their dominant parent P. pulmonarius and P. citrinopileatus. An interspecies hybrids was shows to may have better prospects for genetic improvement in the family of Pleurotus. The sporophores of dominant hybrid (P19xC5) of P. pulmonarius showed crowded bellow lamella, the pilei similar to grey oyster with bigger in size and tougher pileus cap and less spores. These characteristics influenced the harvesting duration and shelf life of the mushroom species. While two other hybrids (P1xC9, and P3xC8) which were similar to P. citrinopileatus sporophores features have less offensive aroma, improved texture and higher sporophores yield, compared to P. citrinopileatus have an attractive shape and yellow in colour but the fragile texture complicates packaging, and its strong aroma is unappealing to consumers. Among the selected hybrids, P19xC5 showed higher growth rate and increased sporophores yield (182.97 g) and biological efficiency (130.19%) followed by hybrids P1xC9 (70.97 %) and P3xC8 (52.14%), which were also higher than the P. citrinopileatus parent (35.63%). Interspecies hybrids obtained by this mating technique can lead to better strains of mushrooms with genetic improvement of Pleurotus species.